PEMAHAMAN ORANG DEWASA AWAL DALAM MEMPERSIAPKAN DIRI MENUJU HIDUP BERKELUARGA - Sari, Reni Eka (Bimbingan dan Konseling, 2014)
In entering the gates of marriage, often a scary thing when the couple began to thinkabout what will happen when they have to be in a marriage. Couples do not or have not beenconcretely imagined their existence in a relationship as husband and wife. The purpose of thisstudy was to describe (1) understanding of early adult seen from the readiness to build domesticharmony. (2) understanding of early adults as seen from the beginning to build family economicreadiness. This type of research used in this study was descriptive quantitative research. Thesample of this study is the sampling area. As for the data disclosure tools that is used in this studyis questionnaire. Furthermore, to obtain the data start adults in 2 RW binuang village in the desertPauh subdistrict headman office Binuang village in Padang Pauh subdistrict. The findings of thestudy illustrate that (1) Understanding of early adults that is seen from the readiness of domesticharmony categorized understanding. (2) understanding of adults as seen from the beginning tobuild family economic readiness categorized less understand readiness to build the familyeconomy. The research findings are recommended for adults, to store the public and parents andmanager Program guidance study and counseling.